2016
DOI: 10.1097/scs.0000000000003026
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Leading to Free Flap Failure

Abstract: BMI, smoking, and operative time were identified as independent risk factors for free flap failure among all flaps or within flap subsets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(32 citation statements)
references
References 24 publications
2
29
1
Order By: Relevance
“…Free flap failure, however, can occur, even when reconstruction is performed by experienced surgeons. Various patient and surgical factors have been associated with free flap failure, including age, diabetes mellitus, smoking history, and operation time [3][4][5][6]. Free flap failure results in additional surgery, prolonged hospital stay, and increased hospital costs [7].…”
Section: Introductionmentioning
confidence: 99%
“…Free flap failure, however, can occur, even when reconstruction is performed by experienced surgeons. Various patient and surgical factors have been associated with free flap failure, including age, diabetes mellitus, smoking history, and operation time [3][4][5][6]. Free flap failure results in additional surgery, prolonged hospital stay, and increased hospital costs [7].…”
Section: Introductionmentioning
confidence: 99%
“…Features such as age, comorbidities, BMI, defect site, and risk factors for vascular disease (such as smoking or diabetes) make flap surgery (especially microsurgical tissue transfer) hazardous but should not be considered as absolute contraindications. 13 A retrospective review demonstrates that age alone is not an independent variable for increased risk in microvascular reconstruction; however, operative time, ASA risk score, and location of the reconstruction site are more associated with the overall success of free tissue transfers. 14 From this point of view, our results suggested that dermal substitutes can be used in a wide range of patients regardless of their general characteristics, as the final outcome is not influenced by the factors analyzed in our sample.…”
Section: Discussionmentioning
confidence: 99%
“…In those studies, the factors that are significantly associated with the loss of the flap are the need for an intraoperative transfusion of three or more units and an elevated surgical time. On the other hand, the relationship to other factors such as age, sex, BMI (body max index), smoking, a history of alcoholism, and the American Society of Anesthesiologist (ASA) score is not so clear [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Different studies have experimentally evaluated, in animal and human models, the effect of perioperative hematocrit on the microvascular success rate. They came up with contradictory results [5,[13][14][15][16]. The effect of anemia on microvascular reconstruction is controversial.…”
Section: Introductionmentioning
confidence: 99%